(untitled) (CAHIERS MAGELLANES-NS, 2024)
Thyroid Eye disease (TED) is also called as Grave’s Orbitopathy (GO). About 20% to 50% of patients with Grave’s disease also have Graves orbitopathy (GO), an autoimmune inflammatory disease of the orbit and periorbital tissues. Low selenium level has been associated with a higher incidence of benign thyroid diseases, such as Grave’s disease and thyroiditis, according to a number of epidemiological studies. TED has a higher prevalence in women than men. The median age of diagnosis is 43 years for all patients, with a range from 8‐88 years. Patients diagnosed over the age of 50 years have a worse prognosis overall. Risk factors for TED include age, gender, ethnicity, and family history. Our objectives were to assess the alterations in serum selenium levels among individuals with thyroid eye disease and to determine any correlations between serum selenium levels and thyroid peroxidase antibodies (TPO) and thyroid related antibodies (TRAb).